2007
DOI: 10.1186/1746-1596-2-25
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus associated gastric carcinoma: a report from Iran in the last four decades

Abstract: Background: Epstein-Barr virus has been proved to be associated with many of the human malignancy including gastric carcinoma, one of the most important human malignancies in the world. There has been no study about the presence of EBV in gastric adenocarcinoma in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 57 publications
7
55
3
1
Order By: Relevance
“…Twenty-two articles [4,8,[13][14][15][16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33][34] were obtained based on the above-mentioned criteria . The samples assayed were collected from 1969 to 2006, and the geographical distribution of the samples examined included 10 countries, i.e., the USA, Brazil, China, Iran, Japan, Kazakhstan, Malaysia, Korea, Mexico, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two articles [4,8,[13][14][15][16][17][18][19][22][23][24][25][26][27][28][29][30][31][32][33][34] were obtained based on the above-mentioned criteria . The samples assayed were collected from 1969 to 2006, and the geographical distribution of the samples examined included 10 countries, i.e., the USA, Brazil, China, Iran, Japan, Kazakhstan, Malaysia, Korea, Mexico, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the current study showed that the stage and metastasis were the significant variables on the survival of the patients affected by gastric cancer, and the highest age was obtained in the seventh decade of life, and also the most common type of cancer diagnosed was adenovirus Published anatomical carcinoma and cardiac and antrum of the stomach, and then according to Zhou et al (3,11), Weibull model was used for the survival of stomach cancer patients in a retrospective study. Hence, 1715 patients with colorectal cancer were examined regarding their age at diagnosis, gender, family history, drug history, tumor location, tumor size, lymph node status, and tumor stage Pathology and depth, which were all selected as potential factors corresponding with the only variable of pathological stage study.…”
Section: Discussionmentioning
confidence: 83%
“…The results of the study conducted by Esmaeeli (48) in Mazandaran province (North of Iran) and by Yazdanbod (28) in Ardabil province (in the north-west of Iran) are almost consistent with the current study, but the findings of studies done by Zera'ati (49) In the present study, the method of treatment was not determined as a factor affecting the patients' survival. But in the studies done in Northern America (53), Sun in China (11,54) and in the Europe (55), a positive effects of complementary chemotherapy and chemotherapy-radiotherapy is reported leading to the patients' survival. Finally, this study showed that the survival of the patients involved with the gastric cancer referring to the Touba Treatment Clinic Center of Sari is in low level, which might be because of the few facilities for on time diagnosis and any strategic program to control this kinds of cancers in Mazandaran province.…”
Section: Iran J Health Sci 2016; 4(3): 61mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the significant decline in the incidence of gastric cancer in the world, especially European countries such as Spain and Italy, which is as the result of the substantial improvement of living conditions, it is passing an ascending trend in developing countries like Iran. Some of this incidence increase is related to improved cancer registry system [35] in the country, and perhaps some proportion of that is due to changes in risk factors of this cancer such as an increase in H. pylori infection [36][37][38][39][40][41]. Surveying the distribution of sex frequency of these patients in the study period shows that the incidence of this cancer is always higher in men.…”
Section: Discussionmentioning
confidence: 99%